Assessment Of The Quality Of Tenderized Chicken Meat Pickle - Murugan M (Department of Poultry Science, College of Veterinary and Animal Sciences, 1998)
A study was carried out to examine the feasibility of preparing chicken pickle using untenderized and tenderized (papain treated) boned spent hen meat, and to evaluate its shelf-life. The ready-to-cook yield and total loss averaged 70. 5±0. 34 per cent and 29. 5±0. 07 per cent respectively for broiler breeder spent hens (72 weeks of age) used for the study. The cooking yields of control (untenderized) and treatment (tenderized) groups were 76.70 and 71.70 per cent respectively. The chicken meat pickle prepared were kept at ambient temperature upto 60 days. Analysis for qualitative assessment on the representative samples was conducted qualitatively and evaluated organoleptically by a taste panel at zero, eight, 16, 24, 32, 40, 48, 56 and 64 days of storage. It was observed that during different periods of storage, the proximate components viz., moisture, protein, fat and total ash of the product significantly altered. As the storage period increased the 2-thiobarbituric acid number (TBA) was also increased significantly (P<0.0l). The total bacterial count increased significantly (P<0.0l) with the increase in the duration of storage. In case of organoleptic evaluation